Comment on: Limit of random measures associated with the increments of a Brownian Semimartingale - LI, Jia (Institutional Knowledge at Singapore Management University, 2018)
We thank the Editors’ invitation for the opportunity of contributing to this special issue as a celebration of Professor Jean Jacod’s seminal work originally written in 1994 (Jacod, 1994). This paper established general limit theorems for integrated volatility functionals, and provided theoretical tools that eventually changed the landscape of theoretical research concerning high-frequency data. This impact is also largely due to Professor Jacod’s continuous contribution to a broad variety of challenging issues in the area of high-frequency financial econometrics, including volatility estimation, jumps, and microstructure noise, as well as a large body of mathematical results collected in Jacod and Shiryaev (2003), Jacod and Protter (2012), and Aït-Sahalia and Jacod (2014).